2015
DOI: 10.1016/j.ijid.2015.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evidence that the opportunistic fungal pathogen Trichosporon asahii is part of the normal fungal microbiota of the human gut based on rRNA genotyping

Abstract: The fungus Trichosporon asahii is distributed widely in the environment and is frequently isolated from clinical specimens. It can cause life-threatening disseminated infections, including breakthrough infection after the administration of candin antifungal drugs. However, the definitive infection route is still unclear. In this study, 43 T. asahii genotypes were detected in 72 fecal samples from healthy subjects. The rRNA genotypes of the species were determined using a culture-independent method. The genotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 9 publications
1
25
0
Order By: Relevance
“…The relative abundance of Candida in activated sludge should mainly derive from municipal wastewater. According to previous reports, Trichosporon species have been isolated from a wide range of substrates, including human hair, soil, and cheese, which should be the sources of the accumulated Trichosporon in activated sludge (Cho et al 2015;Evans and Seviour 2012). Previous reports have indicated that Trichosporon hyphae are involved in the formation of biofilms and sludge flocs and contribute greatly to the degradation of caffeine and sec-hexylbenzene in wastewater (Lakshmi and Das 2013;Nhi-Cong le et al 2016).…”
Section: Resultsmentioning
confidence: 99%
“…The relative abundance of Candida in activated sludge should mainly derive from municipal wastewater. According to previous reports, Trichosporon species have been isolated from a wide range of substrates, including human hair, soil, and cheese, which should be the sources of the accumulated Trichosporon in activated sludge (Cho et al 2015;Evans and Seviour 2012). Previous reports have indicated that Trichosporon hyphae are involved in the formation of biofilms and sludge flocs and contribute greatly to the degradation of caffeine and sec-hexylbenzene in wastewater (Lakshmi and Das 2013;Nhi-Cong le et al 2016).…”
Section: Resultsmentioning
confidence: 99%
“…were recently reported [3538]. A few studies suggested that GI colonization could be one of the potential sources for deep-seated yeast infections [39, 40]. …”
Section: Discussionmentioning
confidence: 99%
“…Trichosporon asahii is a basidiomycetous yeast that has been isolated from environmental sources as well as detected on the skin and in the gut of healthy individuals (Zhang et al ., ; Cho et al ., ). T .…”
Section: Introductionmentioning
confidence: 97%